The Relationship between Vulva Hygiene Behavior and the Risk of Vaginal Discharge (Fluor Albus) in 8th Grade Adolescent Girls at SMPN 1 Parongpong - Faizatun Nisa; Egi Komara Yudha (Health Dynamics, 2024)
Background: Poor personal hygiene behavior can cause vaginal discharge (fluor albus) in adolescent girls. As mentioned by Lawrence Green's theory, three factors can influence a person's health behavior, namely predisposing factors, supporting factors, and reinforcing factors. health behavior, namely predisposing factors, supporting factors, and reinforcing factors. Research Objective: This study aims to find out whether there is a relationship between vulva hygiene behavior and the risk of vaginal discharge (fluorine albus) in 8th grade adolescent girls at SMPN 1 Parongpong. Methods: This study is a correlative analytical study with a cross-sectional approach. The sampling technique in this study uses purposive sampling where sampling is in accordance with the researcher's wishes, namely 67 people from all grade 8 girls at SMPN 1 Parongpong. This study used measuring tools in the form of questionnaires, vulvar hygiene behavior, and the incidence of vaginal discharge. Results: Most or about 34 (50,7%) of 8th grade female adolescent students with a risk of vaginal discharge at SMP N 1 Parongpong had vulvar hygiene behavior with the enough category. Most or about 38 (56,7%) female students in grade 8 with a risk of vaginal discharge at SMP N 1 Parongpong experience physiological vaginal discharge. physiological vaginal discharge. Conclusion: Most or around 34 (50.7%) of 8th grade adolescent girls with vulva hygiene behavior at SMP N 1 Parongpong behaved in the sufficient category. Most or around 38 (56.7%) of 8th grade adolescent girls at risk of vaginal discharge at SMP N 1 Parongpong experience physiological vaginal discharge. There is relationship between vulva hygiene behavior and the risk of vaginal discharge in 8th grade adolescent girls at SMP N 1 Parongpong with a p-value of 0.001.